A New Record on the Morphometric Variations in the Populations of Horseshoe Crab (Carcinoscorpius rotundicauda Latreille) Obtained from Two Different Ecological Habitats of Peninsular Malaysia - Srijaya, T.C.; Pradeep, P.J.; Mithun, S.; Hassan, A.; Shaharom, F.; Chatterji, A. (Our Nature, 2011)
The allometric analysis was used to study the morphometric variability in two different populations of horseshoe crab (Carcinoscorpius rotundicauda, Latreille) collected from Setiu and Gelang Patah (Johor) of Peninsular Malaysia. Values of all parameters in male and female populations of Setiu were recorded high as compared to the horseshoe crab collected from Gelang Patah. In all relationships (total length, carapace length, carapace width and telson length) either with normal values or when values were converted into their logarithmic values, it showed a straight line which indicated that in both populations the increment of all body parts followed an isometric growth. DOI: 10.3126/on.v8i1.4329